2014
DOI: 10.3390/molecules190914022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis with Perfect Atom Economy: Generation of Furan Derivatives by 1,3-Dipolar Cycloaddition of Acetylenedicarboxylates at Cyclooctynes

Abstract: Cyclooctyne and cycloocten-5-yne undergo, at room temperature, a 1,3-dipolar cycloaddition with dialkyl acetylenedicarboxylates 1a,b to generate furan-derived short-lived intermediates 2, which can be trapped by two additional equivalents of 1a,b or alternatively by methanol, phenol, water or aldehydes to yield polycyclic products 3b-d, orthoesters 4a-c, ketones 5 or epoxides 6a,b, respectively. Treatment of bis(trimethylsilyl) acetylenedicarboxylate (1c) with cyclooctyne leads to the ketone 7 via retro-Brook … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A literature survey revealed that, the tetramerization reaction is one of the most fascinating reactions of both dialkyl acetylenedicarboxylic acid derivatives occurring at 25 °C for several days or by heating it alone or in solution for several hours [51,52,53]. Furthermore, trimer [54] and dimer [55] forms were reported for compound 6a . Recently, Huang et al [56] have reported the reaction of 2,2′-bis(azaphosphindole) with four equivalents of 6a in THF at room temperature to afford a tetramer complex of 6a with 2,2′-bis(azaphosphindole).…”
Section: Resultsmentioning
confidence: 99%
“…A literature survey revealed that, the tetramerization reaction is one of the most fascinating reactions of both dialkyl acetylenedicarboxylic acid derivatives occurring at 25 °C for several days or by heating it alone or in solution for several hours [51,52,53]. Furthermore, trimer [54] and dimer [55] forms were reported for compound 6a . Recently, Huang et al [56] have reported the reaction of 2,2′-bis(azaphosphindole) with four equivalents of 6a in THF at room temperature to afford a tetramer complex of 6a with 2,2′-bis(azaphosphindole).…”
Section: Resultsmentioning
confidence: 99%